P.090 The predictors of patient morbidity after adult spinal deformity correction: bone mineral density and the extent of deformity correction. (2nd June 2017) - Ivanishvilli, Z; Hsu, J; Parvez, K; Boisvert, S; Warren, M; Frangou, E; Warren, D
Abstract : Background: Instrumentation failure (IF) such proximal junctional kyphosis/failure or distal junctional failure (PJK/PJF/DJF), rod fracture and screw-loosening can cause morbidity in patients with spinal deformity correction. Factors such as bone mineral density (BMD) or region of deformity correction may play a role in postoperative IF.Methods: We reviewed the relationship between IF and BMD or extent of spinal deformity. IF includes PJK/PJF/DJF, fractured rod, screw-looseing, radiculopathy, and non-union. BMD groups included Normal, osteopenia/osteoporosis, and Unknown. The extent of correction included Lumbar, Short Thoracolumbar (5-8 levels), Long Thoracolumbar (8 to 12 levels), and Cervical-thoracic.Results: 60 patients (41:19 F:M) were included, with average age of 65. Total IF=29 patients (48.3%). Normal BMD in N=14, with half of them (50.0%) developing IF; Low BMD in N=15, with one-third of them (33.3%) developing IF. Lumbar correction was performed in N=19, with IF in 36.8%; Short Thoracolumbar correction was performed in N=28, with IF in 46.4%; Long Thoracolumbar correction was performed in N=11, with IF in 81.8%; and Cervical correction in N=2, with no postoperative IF.Conclusions: Patients that received long-segment thoracolumbar had the highest rates of postoperative morbidity. We did not demonstrate an association between abnormal BMD and postoperative IF. A larger study would be needed for further investigations.